Prognosis of reproduction of malicious generations Lobesia botrana in conditions of plain-steppe of Crimea - Лебедев, С. Н. (Scientific Progress & Innovations, 2012)
Provides information on the intent of the development of malicious generations Lobesia botrana of the leaf roller on vine plantations of plain-steppe Crimea from abiotic factors: the average daily air temperature, amount of precipitation, relative air humidity, as well as the area of leaf surface bush of grapes. On the basis of these data developed mathematical models of forecasting of the development of the phytophage, that allows to optimize the frequency and timeliness of protective measures in the fight against this pest on a particular cultivar of grapes.